2012
DOI: 10.1002/jbm.a.34282
|View full text |Cite
|
Sign up to set email alerts
|

Osteocompatibility evaluation of poly(glycine ethyl ester‐co‐alanine ethyl ester)phosphazene with honeycomb‐patterned surface topography

Abstract: Biodegradable amino acid ester-substituted polyphosphazenes are unique biomaterials for tissue engineering. Considering the surface properties as topography and chemical composition having vital roles in regulating cellular response, in this study, a kind of micropatterned polyphosphazene films were prepared and subjected to osteoblasts culture. Briefly, poly(glycine ethyl ester-co-alanine ethyl ester)phosphazene (PGAP) was synthesized, and its solution in chloroform was cast under high (80%) or low (20%) envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 47 publications
1
36
0
1
Order By: Relevance
“…328 Urushiol-formaldehyde diethylenetriamine polymer (UFDP, 113), a renewable and eco-friendly biopolymer, was also synthesized and used to fabricate BFA films. 329,330…”
Section: Biodegradable Polymersmentioning
confidence: 99%
“…328 Urushiol-formaldehyde diethylenetriamine polymer (UFDP, 113), a renewable and eco-friendly biopolymer, was also synthesized and used to fabricate BFA films. 329,330…”
Section: Biodegradable Polymersmentioning
confidence: 99%
“…After the removal of the side groups from the polymer backbone, P-OH units are formed followed by the migration of the proton from oxygen to nitrogen, which sensitizes the polymer backbone to hydrolysis. The polymer ultimately degrades into nontoxic degradation products comprising mainly of ammonia, phosphoric acid, and the corresponding side groups [5, 18, 26, 30, 45, 61, 66, 87, 88]. A generalized degradation scheme for degradable polyphosphazenes is presented in Fig.…”
Section: Biodegradable Polyphosphazene (Bio-functionalized) and Its Bmentioning
confidence: 99%
“…However, all of these were better than the PLAGA control, which has been widely accepted as a biocompatible material. Studies by Laurencin and coworkers also demonstrated the tissue biocompatibility of biodegradable PPHOS-PLAGA blends [18, 19, 30, 48, 77, 88, 89, 93]. Nair et al [37]have developed biocompatible blends of PNEA and PLAGA (85:15) at two weight ratios of 25:75 and 50:50.…”
Section: Suitability Of Polyphosphazene Blends As Biomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…1. It has been well known that substrates with microroughness could enhance cell attachment and promote cell growth in comparison with smooth-surfaced substrates383940. Accordingly, BMSCs seeded on all the three CNF/BG hybrids demonstrated faster proliferation rates than those cells on pure CNF (Fig.…”
Section: Discussionmentioning
confidence: 88%